2011
DOI: 10.1007/s10549-011-1416-3
|View full text |Cite
|
Sign up to set email alerts
|

Routine pathologic parameters can predict Oncotype DXTM recurrence scores in subsets of ER positive patients: who does not always need testing?

Abstract: Oncotype DX(TM) is an RT-PCR-based assay used to predict chemotherapy benefit in patients with estrogen receptor (ER) positive breast cancers. We were interested if routinely available pathologic parameters could predict Oncotype DX Recurrence Scores (RS) in subsets of patients. We identified 173 breast cancers with available RSs and used 104 of these as a test set and 69 cases as a validation set. Pathologic characteristics including size, histologic type, Nottingham grade, and lymphatic invasion were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
97
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 26 publications
11
97
0
3
Order By: Relevance
“…Although qualitative hormone receptor results appears to be less commonly affected, this variation in quantification has the potential to impact the overall recurrence score, which according to published literature is heavily affected by tumor hormone receptor content, HER2 status, and proliferation. 2,4,26,27 In summary, our study demonstrates good overall concordance for qualitative ER and PR results when comparing immunohistochemistry to qRT-PCR. However, our results suggest immunohistochemistry is more sensitive for both ER and PR detection.…”
Section: Discussionsupporting
confidence: 52%
“…Although qualitative hormone receptor results appears to be less commonly affected, this variation in quantification has the potential to impact the overall recurrence score, which according to published literature is heavily affected by tumor hormone receptor content, HER2 status, and proliferation. 2,4,26,27 In summary, our study demonstrates good overall concordance for qualitative ER and PR results when comparing immunohistochemistry to qRT-PCR. However, our results suggest immunohistochemistry is more sensitive for both ER and PR detection.…”
Section: Discussionsupporting
confidence: 52%
“…Although the Recurrence Score was shown to predict outcome and response to therapy when analyzing large numbers of cases, its prognostic/ predictive accuracy in a given individual patient has not been adequately addressed and little has been done to study the possibility that some cases may have a falsely low or high Recurrence Score when compared with what would be expected based on routine pathological features and/or outcome. 44 In addition, the reproducibility of the assay performed with tissue extracts without microdissection of cancer cells from the stroma is not well established, and several studies suggest that the stromal and intimately associated inflammatory cells, especially when mitotically active, can have a significant effect on the Recurrence Score. 3,44,45 It should also be noted that, in part due to the high cost of the test, no studies validating to the reproducibility and utility of the Oncotype DX assay are available that are independent of Genomic Health.…”
mentioning
confidence: 99%
“…44 In addition, the reproducibility of the assay performed with tissue extracts without microdissection of cancer cells from the stroma is not well established, and several studies suggest that the stromal and intimately associated inflammatory cells, especially when mitotically active, can have a significant effect on the Recurrence Score. 3,44,45 It should also be noted that, in part due to the high cost of the test, no studies validating to the reproducibility and utility of the Oncotype DX assay are available that are independent of Genomic Health.…”
mentioning
confidence: 99%
“…Although both tests were shown to predict outcome and response to therapy when analyzing large numbers of cases, their prognostic and predictive accuracy in a given individual case has not been adequately addressed and little has been done to study the possibility that some cases may have a falsely low-or high-risk prediction when compared with what would be expected based on clinicopathologic features and/or outcome. 17 Furthermore, the reproducibility of the Oncotype DX assay, performed with tissue extracts without microdissection of cancer cells from the stroma, is not well established and several studies suggest that stromal and inflammatory cells can have a significant effect on the Recurrence Score. 2,[17][18][19] Indeed, we have recently shown that a proliferative, cellular stroma and inflammatory cells associated with tumor cells may account for unexpected intermediate-/high-risk estimations by Recurrence Score in low-grade breast carcinomas.…”
mentioning
confidence: 99%
“…17 Furthermore, the reproducibility of the Oncotype DX assay, performed with tissue extracts without microdissection of cancer cells from the stroma, is not well established and several studies suggest that stromal and inflammatory cells can have a significant effect on the Recurrence Score. 2,[17][18][19] Indeed, we have recently shown that a proliferative, cellular stroma and inflammatory cells associated with tumor cells may account for unexpected intermediate-/high-risk estimations by Recurrence Score in low-grade breast carcinomas. 19 In contrast, the immunohistochemistry based Mammostrat assay examines only cancer cells and its results are not affected by the presence of inflammatory cells or the features of tumor stroma.…”
mentioning
confidence: 99%